Odpowiedź :
Odpowiedź:
A = ( 5, 3) B = ( 1, 0)
k : y = 2 x - 7 - wysokość ΔABC
m : y = -0,5 x + b prosta BC
B = ( 1, 0) więc 0 = - 0,5*1 + b ⇒ b = 0,5
m : y = - 0,5 x+ 0,5
D - punkt przecięcia się prostych k i m
2 x - 7 = -0,5 x + 0,5 / * 2
4 x - 14 = - x + 1
5 x = 15
x = 3 ⇒ y = 2* 3 - 7 = - 1
D = ( 3,- 1)
zatem I AD I = h - wysokość ΔABC
A = ( 5,3) i D = ( 3, - 1) więc
h² = I AD I² = ( 3 - 5)² + ( -1 - 3)² = 4 + 16 = 20 =4*5
h = 2√5
------------
P = 0,5*I BC I *h = 0,5* I BC I * 2√5 = √5 I BC I = 5
więc I BC I = √5
C leży na prostej m , zatem C = ( x , -0,5 x +0,5)
oraz B = ( 1, 0), więc I BC I² = ( x - 1)² + ( -0,5 x + 0,5 - 0 )² = ( √5)²
x² - 2 x + 1 + 0,25 - 0,5x + 0,25 x² = 5 / * 4
4 x² - 8 x + 4 + 1 -2 x + x² = 20
5 x² - 10 x - 15 = 0 /: 5
x² - 2 x - 3 = 0 Δ = (-2)² - 4*1*(-3) = 4 + 12 = 16 √Δ = 4
x = [tex]\frac{2 - 4}{2*1} = - 1[/tex] lub x = [tex]\frac{2 + 4}{2} = 3\\[/tex]
zatem y = -0,5*(-1) + 0,5 = 1 lub y = -0,5*3 + 0,5 = -1
zatem
Odp. [tex]C_1 = ([/tex] - 1, 1) [tex]C_2 =([/tex] 3, - 1)
======================================
Szczegółowe wyjaśnienie: